Political Theology and the Dialectics of (Counter)Secularization - Fabbri, Renaud (Politics and religion, 2013)
This article builds on Habermas's hypothesis of a post-secular world society and on Voegelin's philosophy of consciousness. It first analyzes the genesis of the post-secular hypothesis in the work of Habermas. It then looks at the historical roots of the post-secular world society since the Axial Age. Finally, it delineates the evolution of religious actors in modern societies, at the political and cognitive levels, focusing on the European Counter-revolutionaries, the Islamist and post-Islamist movements of the Middle East, and the Hindu Nationalists. The article concludes that Habermas's hypothesis provides a plausible alternative to neo-Schmittian theory of the Clash of Civilizations proposed by Huntington.